Postpartum hemorrhage: New Shar-pei uterine compression technique inrefractory uterine atony. Report on surgicaltechnique in two cases - Collantes Cubas, Jorge Arturo (2026)
Postpartum hemorrhage remains one of the leading causes of maternal mortality,particularly when uterine atony is unresponsive to medical treatment or conventional compression sutures. We report two cases of refractory uterine atony during cesarean section in which, after unsuccessful B-Lynch suture, a new compression technique named Shar-pei was applied. In both cases, bleeding was effectively controlled and hysterectomy was avoided. Postoperative recovery was favorable without major complications. The Shar-pei technique is proposed as a simple, reproducible second-line surgical option, particularly valuable in low-resource settings where uterine preservation is essential.